2017
DOI: 10.1016/j.apsusc.2017.07.181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the tip based micro/nano machining

Abstract: Based on the self-developed three dimensional micro/nano machining system, the effects of machining parameters and sample material on micro/nano machining are investigated. The micro/nano machining system is mainly composed of the probe system and micro/nano positioning stage. The former is applied to control the normal load and the latter is utilized to realize high precision motion in the xy plane. A sample examination method is firstly introduced to estimate whether the sample is placed horizontally. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…5 µm × 5 µm scans used 512 scan lines, for a feed of 9.8 nm. Note that we did not investigate the effect of feed as it has been studied previously (Fang et al, 2006;Guo et al, 2017;Celano et al, 2018). Our feeds were chosen for a favorable compromise between spatial resolution, material removal rate (removing sufficient material to profile through the sample in a reasonable time) and trench smoothness.…”
Section: Methodsmentioning
confidence: 99%
“…5 µm × 5 µm scans used 512 scan lines, for a feed of 9.8 nm. Note that we did not investigate the effect of feed as it has been studied previously (Fang et al, 2006;Guo et al, 2017;Celano et al, 2018). Our feeds were chosen for a favorable compromise between spatial resolution, material removal rate (removing sufficient material to profile through the sample in a reasonable time) and trench smoothness.…”
Section: Methodsmentioning
confidence: 99%
“…Researches have revealed that nanoscratching of hard-brittle materials is a complex process with multiple influencing factors, including scratch speed [6][7][8], shape and geometric parameters of tool [9,10], environment [11], and so on. In addition, many scholars have conducted studies to explore the effect of scratch directions in the processing of materials [12][13][14][15][16]. Yan investigated the material removal state under different scratch directions employing AFM on single crystal copper, it is found that the height of pile-up is greatly influenced by scratch directions [17].…”
Section: Introductionmentioning
confidence: 99%
“…ICRO/NANO positioning system has broad applications in biological manipulation, optical fiber alignment, nano-imprint lithography, scanning probe microscopes, micro/nano assembly and etc [1][2][3][4][5][6]. Compared to conventional macro positioning system, compliant micro/nano positioning system can realize nanometric resolution through the elastic deformation of flexure hinges, which has the advantages of no friction [7][8][9][10][11], no backlash, no lubrication and easy fabrication, whereas the travel range is usually limited from a few microns to several millimeters. In many application fields like probe tip-based micro/nano scratching, there have been quite a few demands of large stroke positioning [12][13][14], and many efforts have been devoted to realizing high precision and large workspace simultaneously.…”
Section: Introductionmentioning
confidence: 99%